2019
DOI: 10.1002/mds.27878
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Activation of Nrf2 Pathway in Parkinson's Disease

Abstract: Background Preclinical studies underlined the relevance of Nuclear factor erythroid 2‐related factor 2 (Nrf2) transcription factor pathway in the pathogenesis of Parkinson's disease (PD). Objective The objective of this study was to explore Nrf2 pathway in vivo in PD, looking for novel disease biomarkers and therapeutic targets. Methods The levels of Nrf2, the downstream effectors (NAD(P)H dehydrogenase [quinone] 1 (Nqo1) enzyme, glutathione metabolism enzymes Glutamate–cysteine ligase (GCL) and Glutathione Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 38 publications
0
62
0
Order By: Relevance
“…The expressions of NRF2 and NQO1 in DAergic neurons derived from iPSCs carrying a PARKIN mutation are also down-regulated [ 97 ]. Recently, a small clinical study demonstrates that levels of NRF2 in peripheral leukocytes are elevated in PD patients [ 183 ]. Larger studies with correlation between NRF2 pathway and clinical severity in PD are warranted to confirm the potential of NRF2 as a biomarker for PD.…”
Section: Candidate Biomarkers For Oxidative Stress In Parkinson’s mentioning
confidence: 99%
“…The expressions of NRF2 and NQO1 in DAergic neurons derived from iPSCs carrying a PARKIN mutation are also down-regulated [ 97 ]. Recently, a small clinical study demonstrates that levels of NRF2 in peripheral leukocytes are elevated in PD patients [ 183 ]. Larger studies with correlation between NRF2 pathway and clinical severity in PD are warranted to confirm the potential of NRF2 as a biomarker for PD.…”
Section: Candidate Biomarkers For Oxidative Stress In Parkinson’s mentioning
confidence: 99%
“…Furthermore, elevated levels of urate, a known NRF2 activator, is protective in a familial form of PD [51]. There was also shown to be a positive correlation between NRF2 transcript levels in PBMCs and disease duration [33] in non-genetically defined PD patients. These studies all suggest that NRF2 expression and function are likely beneficial in the context of PD.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 92%
“…PD is the second most common neurodegenerative disorder, characterized by progressive motor and non-motor disturbances, due to the loss of dopaminergic cells in the substantia nigra pars compacta (SNpc) and the accumulation of α-synuclein (α-syn)-positive Lewy bodies [7][8][9]. The relationship between viral infections and PD has its roots in the early twentieth century, when a number of post-encephalitic parkinsonism were observed following an influenza outbreak.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Further experimental evidence showed that Influenza-A virus disrupts mitochondrial activity and increase oxidative stress [ 12 , 13 ], whereas hepatitis C virus impairs dopaminergic transmission and affects the blood–brain barrier (BBB) integrity [ 10 ]. Therefore, viral infections may intervene in cellular pathways critical for PD pathogenesis, probably contributing to the initiation of the disease [ 8 , 9 , 14 17 ].…”
Section: Parkinson’s Diseasementioning
confidence: 99%